Decolonization in Saint Lucia : Politics and Global Neoliberalism, 1945-2010. - Joseph, Tennyson S. D. (Caribbean Studies Series., 2011)
Tennyson S.D. Joseph builds upon current research on the anticolonial and nationalist experience in the Caribbean. He explores the impact of global transformation upon the independent experience of St. Lucia and argues that the island's formal decolonization roughly coincided with the period of the rise of global neoliberalism hegemony. Consequently, the concept of "limited sovereignty" became the defining feature of St. Lucia's understanding of the possibilities of independence. Central to the analysis is the tension between the role of the state as a facilitator of domestic aspira.